2018
DOI: 10.1007/s00268-018-4606-x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Circular Stapler Diameter and Stricture Rates Following Gastrointestinal Anastomosis: Systematic Review and Meta-analysis

Abstract: The use of larger circular stapler sizes is strongly associated with reduced risk of anastomotic stricture in the upper GI tract, though data from lower GI joins are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 67 publications
0
16
3
1
Order By: Relevance
“…[23][24][25][26][27][28] It was concluded that the use of larger circular stapler size (28 mm versus 25 mm) was strongly associated with a reduced risk of postoperative anastomotic strictures in the upper GI tract. 22 Results from our study do not support the conclusion of aforementioned meta-analysis, as there were no differences observed in anastomotic insufficiency and postoperative anastomotic strictures between the 25 mm and the 28 mm stapled esophagogastric anastomosis. The meta-analysis included 367 patients in the 25 mm and 460 patients in the 28 mm group (827 patients in total).…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…[23][24][25][26][27][28] It was concluded that the use of larger circular stapler size (28 mm versus 25 mm) was strongly associated with a reduced risk of postoperative anastomotic strictures in the upper GI tract. 22 Results from our study do not support the conclusion of aforementioned meta-analysis, as there were no differences observed in anastomotic insufficiency and postoperative anastomotic strictures between the 25 mm and the 28 mm stapled esophagogastric anastomosis. The meta-analysis included 367 patients in the 25 mm and 460 patients in the 28 mm group (827 patients in total).…”
Section: Discussioncontrasting
confidence: 95%
“…The meta-analysis included 367 patients in the 25 mm and 460 patients in the 28 mm group (827 patients in total). 22 Our study included 349 patients (222 in the 25 mm group and 127 in the 28 mm group) and might significantly contribute (30% additional patients) evidence that there is no difference in postoperative outcomes between the two stapler diameters applied for a circular stapled intrathoracic anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the anastomotic technique may have an impact on the incidence of dysphagia, as there is evidence of lower stricture rates after mechanical sideto-side anastomosis compared with circular stapler or manual suture anastomosis [15][16][17]. Likewise, a correlation between smaller circular stapler diameter (25 cm) and higher stricture rate has been evidenced in a systematic review [18]. Recurrent nerve palsy is also more common after cervical esophagogastrostomy and confers an increased risk of aspiration [19].…”
Section: Pathophysiology and Symptomsmentioning
confidence: 99%